Analisis Strategi Kementerian Pendayagunaan Aparatur Negara Dan Reformasi Birokrasi Dalam Mencegah Pelanggaran Netralitas ASN Pada Pemilhan Umum 2024 - Putri, Rossela Arneta; Silmi, Vici Rahma; Kurnia, SettingsMuhammad Rafli; Hermawan, Muhammad Radityo (Indonesian Democracy Research Center, 2024)
The 2024 elections in Indonesia raise concerns about violations of ASN neutrality, which could lead to violations of the ASN code of ethics during the elections. This research analyzes the effectiveness of the Ministry of Administrative Reform and Bureaucratic Reform's strategy in preventing these violations. A qualitative descriptive approach was used through literature study, field observations and interviews with interested parties. The research results show that, in addition to strengthening regulations through a Surat Keputusan Bersama (SKB) concerning Guidelines for the Development and Supervision of ASN Neutrality, increased coordination between institutions is needed to maintain ASN neutrality during elections. Apart from that, wider socialization is also important. Even though regulations already exist, based on a report released by the National Commission for State Civil Apparatus (KASN), 124 cases of violations were recorded, with around 40% involving violations of the ASN code of ethics in the 2024 elections, indicating that there are still violations that result in low flexibility in holding elections. Evaluation of the inter-institutional coordination mechanisms contained in the SKB, the content of training and education on ASN neutrality, supervision of acts of violation of ASN neutrality as well as the reporting system for violations of ASN neutrality are necessary to realize general elections that are free from acts of violations permitted by state civil servants.